(untitled) (Physical Education, Health and Social Sciences, 2026)
Diabetes mellitus is one of the major non-communicable diseases and the prevalence is rising globally. Diabetes is a leading cause of preventable blindness in adults aged between 20-75 years. Diabetes is increasingly recognized as the leading cause of chronic renal failure and hepatic disease. The aim of the study was to determine the function of liver and kidney of diabetic patients. A total of 40 blood samples from the diabetic patients were selected and then categorized into age wise ranging from 40 to 80 years and gender wise distribution. Using the commercially available kits according to the manufacturer’s instructions. Blood urea, creatinine, ALT, bilirubin and ALP was estimated by the Microlab-300 Labtech reagent kit on the selected samples. Our result concluded that the renel function of diabetic patient’s age ranging above 40 to 60 were slightly elevated than normal and the age ranging from 61 to 80 were more affected. The liver function of diabetic patients showed normal results age ranging from 40 to 50 years and the age ranging from 61 to 80 are slightly elevated. The renal function of diabetic patients were more elevated as compare to liver function. It is further concluded that in gender wise distribution females were more affected than males during RFTs analysis. Similarly in LFTs analysis males were more affected is compared to females.